2009
DOI: 10.1126/science.1177980
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Half-Quantum Vortices in an Exciton-Polariton Condensate

Abstract: Singly quantized vortices have already been observed in many systems, including the superfluid helium, Bose-Einstein condensates of dilute atomic gases, and condensates of exciton-polaritons in the solid state. Two-dimensional superfluids carrying spin are expected to demonstrate a different type of elementary excitations referred to as half-quantum vortices, characterized by a p rotation of the phase and a p rotation of the polarization vector when circumventing the vortex core. We detect half-quantum vortice… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
306
1
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 340 publications
(318 citation statements)
references
References 23 publications
4
306
1
7
Order By: Relevance
“…In the circular polarization basis, a HQV results in a full 2p phase shift in one polarization and no phase shift in the other. This feature significantly simplifies the detection method as we make use of a polarization mixing Mach-Zehnder interferometer 24 (see Methods section), in the mirrorretroreflector configuration (Fig. 1a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the circular polarization basis, a HQV results in a full 2p phase shift in one polarization and no phase shift in the other. This feature significantly simplifies the detection method as we make use of a polarization mixing Mach-Zehnder interferometer 24 (see Methods section), in the mirrorretroreflector configuration (Fig. 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Being the lowest energy topological excitations, they are essential in determining the Kosterlitz-Thouless phase transition in spinor quantum fluids 22 . Convincing experimental evidence of HQVs was recently provided in a spinor polariton condensate 24 , where the properties of the system allow for direct imaging of both the amplitude and phase of the condensate wave function. Signs of fractional vorticity were previously only reported in hightemperature superconductors 25 , later indirectly measured in spin-triplet superconductors 26 and identified as a result of the decay of 2D Skyrmions in atomic condensates 27 , while their observation is still elusive in other spinor systems like He3 thin films 28 .…”
mentioning
confidence: 99%
“…Therefore, a fork-like defect in a phase pattern can be a signature of a quantized vortex. Fork-like defects in interference patterns were reported for optical vortices, see [45] and references therein, vortices in atom condensates [46][47][48], and polariton vortices [49,50].…”
Section: Phase Singularities: Fork-like Defects In Exciton Interferenmentioning
confidence: 96%
“…Their existence was first predicted in superfluids [1,2], and later in coherent waves [3]. Nowadays, quantised vortices have been the subject of extensive research across several areas of physics and have been observed in type-II superconductors, 4 He, ultracold atomic gases, non-linear optical media (for a review see, e.g., [4]) and very recently microcavity polaritons [5,6,7,8,9,10,11,12], the coherent strong mixing of a quantum well exciton with a cavity photon. adding a pulsed Gaussian probe to the OPO regime (the so called TOPO regime) in Sec.…”
Section: Introductionmentioning
confidence: 99%